The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12978-019-0845-z
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence related disclosure among women and girls in Ethiopia: a systematic review and meta-analysis

Abstract: BackgroundDomestic violence is common public health problem. Domestic violence related disclosure is an important first step in the process of prevention, control and treatments of domestic violence related adverse effect. Thus, this systematic review and meta-analysis aimed to determine the pooled prevalence of domestic violence related disclosure and synthesize its associated factors.MethodsWe followed the PRISMA Guidelines to report the results of the finding. Databases including PubMed, Cochrane Library an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Consideration of findings from this analysis should take into account the following limitations. First, the VACS are self-reported questionnaires, and thus measures of sensitive items such as suicide ideation and violence exposure may be susceptible to disclosure bias [ 25 , 26 , 27 ]. Second, our measure of mental well-being was constructed using only six survey questions and may not serve as a robust measure of mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of findings from this analysis should take into account the following limitations. First, the VACS are self-reported questionnaires, and thus measures of sensitive items such as suicide ideation and violence exposure may be susceptible to disclosure bias [ 25 , 26 , 27 ]. Second, our measure of mental well-being was constructed using only six survey questions and may not serve as a robust measure of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In its 2017 white paper, the International Center for Research on Women (ICRW) reported the effect of unequal gender norms, and the role conflict they cause in adolescents, on augmenting suicidal behavior risks [ 23 ]. Furthermore, a wide body of literature evidences a negative correlation between IPV tolerance and help-seeking behavior among GBV survivors [ 24 ], commonly attributed to fear of stigma and reprisals from partners and family members due to disclosure [ 25 , 26 , 27 ]. Together, these trends support the possibility that attitudinal acceptance of IPV might modify the relationship between IPV victimization and mental health outcomes and suggest two hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2016 Ethiopian Demographic and Health Survey (EDHS2016), out of 34% of women who have experienced IPV, 66% of them were not told to any one [ 18 ]. During pregnancy, the prevalence of physical, sexual, psychological, and overall prevalence of IPV was ranging from 2% to 35%, 9% to 40%, 22% to 65% [ 19 ], and 0.9% to 57% [ 5 , 20 , 21 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although many of the risk factors were similar among pregnant and nonpregnant women, various studies have shown that pregnancy could be one of the risk factors for the initiation or escalation of IPV for certain women. Generally, factors including (i) pregnancy-related such as unplanned pregnancy, unwanted pregnancies, and elective termination of pregnancy; (ii) victim-related characteristics such as age, marital status, ethnicity, education, employment, substance use; and (iii) perpetrator-related characteristics such as dependency, jealousy, and possessiveness towards female partner were factors associated with IPV during pregnancy [ 5 , 20 , 21 ]. In spite of the high prevalence of IPV and its associated adverse impact, there is a dearth of epidemiological evidence in Ethiopia and only a systematic review and meta-analysis were reported from eight studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, one in three women do not disclose partner abuse in Ethiopia. 9 Ballard et al identified four patterns of perinatal partner violence that measure persistence, including: violence begins (starts at pregnancy), violence continues (before and during pregnancy), violence ceases (before but not during pregnancy), and no violence (no violence at any stage). 10 Presumably, IPV has no limits, occurring during reproductive life, but women are more likely to experience violence during pregnancy and postpartum.…”
Section: Introductionmentioning
confidence: 99%